2010
DOI: 10.1002/etc.308
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of tetra‐ and pentabromo diphenyl ether and benzo[a]pyrene among water and dissolved and particulate organic carbon along a salinity gradient in coastal waters

Abstract: This study assessed the partitioning of 2,2',4,4'-tetrabromo diphenyl ether (BDE-47), 2,2',4,4',5-pentabromo diphenyl ether (BDE-99) and benzo[a]pyrene (BaP) among water, dissolved organic carbon (DOC: 4.93-8.72 mg/L), and particulate organic carbon (POC: 191-462 µg/L) along the salinity gradient (0-5.5‰) of the Baltic Sea off the coast of Finland. Equilibrium dialysis and two solid-phase extraction techniques using polyoxymethylene polymer (POM) were used to determine partitioning coefficients. Experiments us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…The distribution constant between water and DOC (log K DOC ) for hexachlorobenzene and phenanthrene, representing halogenated aromatic and polycyclic aromatic compounds, respectively, decreased from north to south in the Baltic Sea, while tributyl phosphate, representing compounds with polar functional groups and relatively high water solubility, showed no geographical variation. The salinity gradient in the study, from 2.8 to 6.6, probably had only a minor effect on the partitioning of the tested organic pollutants (Engebretson and von Wandruszka 1994 ; Kuivikko et al 2010 ). Considering the small variation of DOC concentration in the offshore Baltic Sea (4.2–5.2 mg C/l), we propose that differences in quality, i.e., the terrestrial component of the DOC, caused the differences in log K DOC values.…”
Section: Effects Of Increased Doc Inflow On Organic Pollutant Sorptiomentioning
confidence: 85%
“…The distribution constant between water and DOC (log K DOC ) for hexachlorobenzene and phenanthrene, representing halogenated aromatic and polycyclic aromatic compounds, respectively, decreased from north to south in the Baltic Sea, while tributyl phosphate, representing compounds with polar functional groups and relatively high water solubility, showed no geographical variation. The salinity gradient in the study, from 2.8 to 6.6, probably had only a minor effect on the partitioning of the tested organic pollutants (Engebretson and von Wandruszka 1994 ; Kuivikko et al 2010 ). Considering the small variation of DOC concentration in the offshore Baltic Sea (4.2–5.2 mg C/l), we propose that differences in quality, i.e., the terrestrial component of the DOC, caused the differences in log K DOC values.…”
Section: Effects Of Increased Doc Inflow On Organic Pollutant Sorptiomentioning
confidence: 85%
“…Solutions of BDE-153, containing SRFA or PLFA, were prepared and exposed to simulated sunlight as detailed above. Experiments were conducted with addition of NaN 3 (10 mM, quenchers of 1 O 2 ) and IPA (100 mM, quenchers of OH) to investigate indirect photolytic mechanisms (Latch et al, 2003).…”
Section: Indirect Photolysismentioning
confidence: 99%
“…Leal et al (2013) reported that the photolytic percentage of BDE-209 decreased substantially in the presence of humic and fulvic acids and attributed their findings to two main effects: (i) screening effects from radiation absorption by humic substances and (ii) hydrophobic associations between BDE-209 and humic acid that promote quenching or deactivation of the excited-state. Further, humic substances affect the adsorption of organic contaminants to aquifer material and sorption of PBDEs to dissolved humic substances in aqueous solutions (Rav-Acha and Rebhun, 1992; Kuivikko et al, 2010). Chu et al (2005) attributed the decrease of the photolytic rate of PCBs, which have structural similarities to PBDEs, to the decrease in lifetimes of their excited singlet or triplet states caused by binding to humic substances.…”
Section: Bde-153 Photolysis In the Presence And Absence Of Nommentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been developed to separate freely dissolved organic contaminants from DOM-bound species, including equilibrium dialysis, ultracentrifugation [8], reversephase separation, solid-phase microextraction [9], competing ligands [10], and ultrafiltration. For example, cross-flow ultrafiltration followed by gas chromatography-mass spectrometry has been used to determine the partitioning of organic contaminants between river colloids and the dissolved phase [11].…”
Section: Introductionmentioning
confidence: 99%